Tracing experiment in the Ledvica Lake in the Triglav Lakes Valley - Urbanc, Janko; Brancelj, Anton (Geologija, 1999)
The paper presents the tracing experiment which was carried out in June 1999 in the area of the Triglav lakes. Uranine was injected into the Ledvica lake. Changes in tracer concentration were used to estimate the recharge rate of the water in the lake. The tracing experiment also showed a hydraulic connection with the lower-located lakes and springs: Močivec, Dvojno jezero, the spring under Rušnata glava and the Savica.